Project-Based English Language Instruction: A Study of Secondary School Learners in India - Syed Faiz Zaidi (Universitas Negeri Makassar, 2014)
The idea of Project-Based Learning (PBL) is based on a holistic instructional strategy, which is becoming more meaningful in today’s society as teachers increasingly teach groups of young learners having different learning styles and ability levels. These learners primarily come from the northern part of India and have not been properly exposed to the learning of English because of varied linguistic, cultural, schooling and social backgrounds. The study aims at assessing the effectiveness of PBL in teaching young learners (14-16 years of age) Aligarh Muslim University, India. The methods employed in the study rely on data obtained with both qualitative and quantitative research instruments. Keywords: Project-based language instructions, project-based learning